Capturing affective well-being in daily life with the day reconstrution method: A refined view on positive and negative affect - Dave Möwisch; Florian Schmiedek; David Richter; Annette Brose (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
In the last years, there has been a shift from traditional measurements of affective well-being to approaches such as the day reconstruction method (DRM). While the traditional approaches often assess trait level differences in well-being, the DRM allows examining affective dynamics in everyday contexts. The latter may ultimately explain why some people feel more happy than others (e.g., because they experience more gratification during everyday experiences). Even though DRM research has increased in the last years, little is known about the structure of affective well-being in everyday life, and potential structural differences of affect at the within- and between-person level have rarely been considered. We thus thoroughly examined the structure of affective well-being in daily life, using data from a nationally representative sample (N = 2401) of the German Socioeco-nomic Panel Innovation Sample that were obtained with the DRM. Multilevel structural equation models revealed that (1) affective well-being in daily life cannot be reduced to the two global dimensions positive and negative affect (PA and NA) but that the structure of NA is more nuanced; (2) the emerging subfacets of NA have distinct associations with global indicators of well-being (e.g., life satisfaction); (3) there are structural differences of affective well-being at the within- and between-person level, and (4) the relationships between affect subfacets and activities such as "work" can be opposed at the within- and between-person level. These results show that a more differentiated view on the structure of affect contributes to a better understanding of affective well-being in everyday life.
Keywords: 330; Day reconstruction method; Positive affect; Negative affect; Multilevel structural equation modeling; Subjective well-being